Health risk assessment and determination of bisphenol A and aflatoxin M1 in infant formula - Ghazal Mirzaei; Najmeh Yazdanfar; Nabi Shariatifar; Ebrahim Molaee -Aghaee; Parisa Sadighara (BMC Nutrition)
Abstract Background Bisphenol A (BPA) is one of the chemical compounds used in food packaging, so it can migrate from the packaging into food. Also, environmental pollution of this compound is high due to its high use. Therefore, it may enter food chains through the environment. Aflatoxin M1 (AFM1) is one of the common mycotoxins in milk. Its presence has been reported worldwide. Infant formula is an alternative to human milk. The main ingredient of this product is cow’s milk. Aims This study aimed to investigate the levels and risk assessment of BPA and aflatoxin M1 in infant formula. Methods Samples were purchased from 7 leading brands of infant formula in pharmacies. The samples were extracted according to common protocols and then injected into HPLC and analyzed with a fluorescence detector for both contaminants. Results BPA wasn’t detected in infant formula samples, but the presence of AFM1was confirmed in 11% of the samples. Of course, there is no risk in this regard with the risk assessment. Conclusion Infant formula samples are not of concern for infants in terms of BPA and aflatoxin M1. However, continuous monitoring is recommended for this product.